A third generation improved Zr-4 alloy and its preparation method and application

By adding trace amounts of W, Cu, Ni and Ta elements to the second generation Zr-4 zirconium alloy to form a replacement solid solution, the uneven corrosion problems of zirconium alloy in long-term uniform corrosion and boil-like corrosion tests were solved, and significantly improved the Its high-temperature mechanical properties meet the standards of the third-generation zirconium alloy.

CN118222883BActive Publication Date: 2025-02-07XIAN WESTERN ENERGY MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410228683.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-29
Publication Date
2025-02-07
Estimated Expiration
2044-02-29

AI Technical Summary

Technical Problem

The existing second-generation improved Zr-4 zirconium alloy has uneven corrosion in long-term uniform corrosion and boil-like corrosion tests, and has insufficient mechanical properties to resist high temperatures, especially poor thermal creep performance.

Method used

By adding trace W elements, Cu elements, Ni elements and Ta elements to the second generation improved Zr-4 alloy, the Zr-W-Cu-Ni-Ta substitution solid solution is formed, and the corrosion and mechanical properties of the alloy are improved. Specific steps include ingredients, mixing, pressing electrode blocks, welding, vacuum consumable arc smelting, etc.

Benefits of technology

It significantly improves the resistance to uniform corrosion, boil-like corrosion, and high-temperature mechanical properties of zirconium alloys, including thermal creep, fatigue and wear properties, reach or exceed the level of third-generation zirconium alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118222883B_ABST
    Figure CN118222883B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of zirconium alloy materials, and relates to a third-generation improved Zr-4 alloy and a preparation method and application thereof. The alloy comprises: Sn 0.85% to 1.50%, Fe 0.18% to 0.24%, Cr0.07% to 0.13%, O 0.09% to 0.16%, W 0.002% to 0.009%, Cu 0.002% to 0.008%, Ni 0.002% to 0.008%, Ta 0.002% to 0.009%, and the remainder is Zr and unavoidable impurities. The preparation of the alloy optimizes the addition method of the elements: O element is added in the form of tin metal oxide; Ta element is added in the form of an intermediate alloy such as copper-tantalum alloy; W element is added in the form of tungsten metal oxide, and the obtained Zr-4 alloy has excellent uniform corrosion resistance, nodular corrosion resistance, high temperature fatigue resistance, creep, wear and other properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of zirconium alloy materials and relates to a Zr-4 alloy, and in particular to a third-generation improved Zr-4 alloy and a preparation method and application thereof. Background Art

[0002] Zirconium and its alloy materials have extremely strong corrosion resistance, extremely small thermal neutron absorption cross section, and good mechanical properties after irradiation, so they are widely used in fuel cladding materials and structural materials of nuclear reactors. The research and application of zirconium alloys in nuclear reactors began in the 1950s, and it has been more than 70 years so far. Except for some scientific research reactors, zirconium alloys are still the only cladding material for commercial water-cooled nuclear reactors. It is well known in the industry that the main development of zirconium alloys has gone through three generations: the first generation is the two zirconium alloys Zr-2 and Zr-4 developed by the United States; the second generation is the second generation improved Zr-4 alloy after reducing the tin content and increasing the iron and chromium content on the basis of the first generation Zr-4 alloy, also known as low-tin Zr-4 alloy; the third generation zirconium alloy is niobium-containing zirconium alloy, which is divided into zirconium-niobium series and zirconium-tin-niobium series, mainly including Zirlo, E635, M5, N36 and other grades. Except for a few zirconium-niobium alloys such as M5 and Zr-2.5Nb, other third-generation zirconium alloys are zirconium-tin-niobium alloys. Compared with the second-generation zirconium alloy, the main advantages of the third-generation zirconium alloy are: after adding no less than 0.1% niobium element, the nodular corrosion phenomenon is eliminated and the nodular corrosion resistance is significantly improved; although this slightly reduces the uniform corrosion performance to a certain extent, it has the advantages of stronger comprehensive corrosion performance, stronger mechanical properties, stronger safety and longer service life.

[0003] At present, the third-generation zirconium alloy is in the trend of large-scale application in the world, such as France M5, the United States Zirlo, my country N36 and other brands are expanding their application range on a large scale. However, the second-generation improved Zr-4 alloy is still in large-scale use, especially for boiling water reactors, heavy water reactors and other reactor types. Zr-4 alloy must still be used. This is because the corrosion weight gain of the second-generation improved Zr-4 alloy is significantly less than that of the third-generation zirconium alloy in the long-term uniform corrosion test. However, in the long-term uniform corrosion test of the second-generation improved Zr-4 alloy, although the corrosion weight gain is less than that of the third-generation zirconium alloy, it still has obvious problems. For example, in the long-term uniform corrosion test at 400℃, 10.3MPa, and 300 days, gray-white or yellow-brown corrosion spots will appear locally on its surface, which are called "white spots" or "yellow spots" in the industry. The initial generation of the corrosion spots will not affect the corrosion weight gain, but after about 1 or 2 cycles of corrosion transition, the corrosion weight gain will be significantly increased, and the spots will be significantly raised, resulting in uneven corrosion. After continuing the long-term corrosion test, it will eventually cause local damage to the alloy surface. Furthermore, the second-generation improved Zr-4 alloy has poor nodular corrosion resistance, which is significantly inferior to the third-generation zirconium alloy. Specifically, in the nodular corrosion test at 500°C, 10.3MPa, and 8h, some nodular corrosion spots will appear on the sample. After 36h of nodular corrosion test, the surface of the sample will be damaged in a large area due to nodular corrosion. After 200h of nodular corrosion, the sample will be completely broken; while the third-generation zirconium alloy can achieve no nodular corrosion spots after 200h of nodular corrosion test. In addition, the high-temperature mechanical properties of the second-generation improved Zr-4 alloy are not good enough, especially the thermal creep performance is far behind the third-generation zirconium alloy. Therefore, there is a wide and urgent application demand for improving the performance of Zr-4 alloy, such as improving its uniform corrosion resistance, especially nodular corrosion resistance, and further improving mechanical properties such as creep, high-temperature fatigue, and high-temperature wear.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned shortcomings of the prior art and provide a third-generation improved Zr-4 alloy and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a third-generation improved Zr-4 alloy, consisting of the following components in mass percentage: Sn 0.85% to 1.50%, Fe 0.18% to 0.24%, Cr 0.07% to 0.13%, O 0.09% to 0.16%, W 0.002% to 0.009%, Cu 0.002% to 0.008%, Ni 0.002% to 0.008%, Ta 0.002% to 0.009%, and the balance is Zr and unavoidable impurities.

[0008] Specifically, the third-generation improved Zr-4 alloy may be composed of the following components in mass percentage: Sn 1.0% to 1.2%, Fe 0.21% to 0.24%, Cr 0.08% to 0.11%, O 0.13% to 0.15%, W 0.004% to 0.007%, Cu 0.003% to 0.005%, Ni 0.004% to 0.006%, Ta 0.005% to 0.008%, and the balance is Zr and unavoidable impurities.

[0009] Specifically, the third-generation improved Zr-4 alloy may be composed of the following components in mass percentage: Sn 1.1% to 1.3%, Fe 0.20% to 0.23%, Cr 0.09% to 0.12%, O 0.14% to 0.16%, W 0.003% to 0.006%, Cu 0.004% to 0.006%, Ni 0.003% to 0.005%, Ta 0.004% to 0.007%, and the balance is Zr and unavoidable impurities.

[0010] Specifically, the third-generation improved Zr-4 alloy may be composed of the following components in mass percentage: Sn 1.2% to 1.4%, Fe 0.19% to 0.22%, Cr 0.11% to 0.13%, O 0.12% to 0.14%, W 0.005% to 0.008%, Cu 0.003% to 0.005%, Ni 0.005% to 0.007%, Ta 0.003% to 0.006%, and the balance is Zr and unavoidable impurities.

[0011] Specifically, the third-generation improved Zr-4 alloy may be composed of the following components in mass percentage: Sn 1.3% to 1.5%, Fe 0.21% to 0.24%, Cr 0.09% to 0.12%, O 0.12% to 0.14%, W 0.004% to 0.007%, Cu 0.004% to 0.006%, Ni 0.004% to 0.006%, Ta 0.004% to 0.007%, and the balance is Zr and unavoidable impurities.

[0012] Specifically, the third-generation improved Zr-4 alloy may be composed of the following components in mass percentage: Sn 0.9% to 1.1%, Fe 0.20% to 0.23%, Cr 0.08% to 0.11%, O 0.13% to 0.15%, W 0.003% to 0.006%, Cu 0.005% to 0.007%, Ni 0.003% to 0.005%, Ta 0.005% to 0.008%, and the balance is Zr and unavoidable impurities.

[0013] In a second aspect, the present invention provides a method for preparing the third generation improved Zr-4 alloy as described above in part or in whole, which specifically comprises the following steps:

[0014] Step 1, prepare and mix the ingredients according to the mass percentage of each element in the third-generation improved Zr-4 alloy described in part or all of the above, wrap the raw materials with zirconium foil or tin foil, and press them into electrode blocks;

[0015] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0016] Step 3: performing vacuum consumable arc melting on the zirconium alloy consumable electrode for 2 to 4 times to obtain a third-generation improved Zr-4 alloy ingot.

[0017] Furthermore, the raw materials include nuclear grade sponge zirconium, master alloy, tin metal oxide, tungsten metal oxide and the like.

[0018] The above third-generation improved Zr-4 alloy mainly improves the alloy performance through the following five aspects, as follows:

[0019] 1. The addition of O element improves the uniform corrosion performance of Zr-4 alloy:

[0020] The present invention abandons the traditional method of adding O element by zirconium dioxide, and adds O element by tin oxides such as tin dioxide (SnO2), tin monoxide (SnO), tin tetraoxide (Sn3O4), etc., which can significantly improve the uniform corrosion resistance of zirconium alloy, especially the long-term uniform corrosion resistance. In addition, in the long-term uniform corrosion test at 400°C, 10.3MPa, and 300 days, its corrosion weight gain is reduced to about 80% of the second-generation improved Zr-4 alloy (using zirconium dioxide to add O element); when the long-term uniform corrosion reaches 600 days, its corrosion weight gain is reduced to about 85% of the second-generation improved Zr-4 alloy (using zirconium dioxide to add O element), or even lower, which obviously surpasses the long-term uniform corrosion resistance of all third-generation zirconium alloys. This is because: the traditional method of adding oxygen elements to zirconium metal oxides such as zirconium dioxide ignores the extremely high melting point of zirconium dioxide (2700℃). Adding oxygen elements to zirconium dioxide will cause a considerable portion of zirconium dioxide to be unable to melt and decompose during smelting, and it will still be dispersed in the alloy as micron- and nano-scale zirconium dioxide particles. Ultimately, in the long-term uniform corrosion test of zirconium alloys, when the tetragonal phase generated by corrosion oxidation transforms into a monoclinic phase, the dispersed zirconium dioxide falls off, further increasing the irregularity of the corrosion interface between zirconium oxide and the zirconium matrix, resulting in an increase in the reaction rate between water and the zirconium matrix.

[0021] Therefore, the present invention adopts tin dioxide and other tin metal oxides to add oxygen elements (excluding oxygen elements introduced by other raw materials such as sponge zirconium and tungsten metal oxides), which effectively avoids this shortcoming. The melting point of tin dioxide is 1630°C, the melting point of tin monoxide is 1080°C, the melting point of metal zirconium is 1852°C, and the melting temperature of zirconium alloy is usually about 2000°C. Therefore, during the smelting process, it can be ensured that the added oxide can be completely dissolved, so that the oxygen element is evenly dispersed in the α-Zr phase of the zirconium alloy, effectively forming an interstitial solid solution of the α-Zr phase, and finally strengthening the corrosion resistance of the α-Zr phase of the zirconium alloy.

[0022] 2. The third generation improved Zr-4 alloy provided by the present invention adds trace amounts of W, Cu and Ni elements on the basis of the second generation improved Zr-4 alloy to significantly improve the uniform corrosion resistance of the zirconium alloy, especially the long-term uniform corrosion resistance. Specifically, in the second generation improved Zr-4 alloy, the addition of (20-200) ppm of Cu alone has no obvious effect on improving the uniform corrosion resistance of the zirconium alloy, and there is no obvious regularity in the influence on the uniform corrosion resistance of the zirconium alloy. In the second generation improved Zr-4 alloy, the addition of (20-200) ppm of W or Ni alone can improve the uniform corrosion resistance; however, in the long-term uniform corrosion test at 400°C, 10.3MPa and 300 days, gray-white or yellow-brown corrosion spots will still appear locally on the surface of some alloy samples. The initial generation of the corrosion spots will not affect the corrosion weight gain, but after several corrosion transitions, the corrosion weight gain will be significantly increased, and finally uneven corrosion will occur. Moreover, the inventors have found that when the amount of W added is greater than 90ppm, the hardness of the alloy will be significantly increased, and the plasticity of the zirconium alloy will be significantly reduced. Too much W will make the processing of the zirconium alloy more difficult. When the amount of Ni added is greater than 80ppm, the hydrogen absorption rate of the zirconium alloy will increase, and the more the amount added, the more obvious it is. Too much Ni will worsen the long-term uniform corrosion performance of the zirconium alloy. In this regard, the inventors of this application conducted the following research:

[0023] ① First, W and Ni are added to the second-generation improved Zr-4 alloy, and the amount of W added is reduced to (20-90) ppm and the amount of Ni added is reduced to (20-80) ppm, which can improve the uniform corrosion resistance. In the long-term uniform corrosion test at 400℃, 10.3MPa, and 300 days, most alloy samples have a black and shiny oxide film, but gray-white or yellow-brown corrosion spots will still appear locally on the surface of very few samples; the initial generation of these corrosion spots will not affect the corrosion weight gain, but after several corrosion transitions, the corrosion weight gain will increase significantly, and eventually uneven corrosion will occur.

[0024] ② When W and Cu are added to the second-generation improved Zr-4 alloy, and the W addition is reduced to (20-90) ppm, and the Cu addition is reduced to (20-80) ppm, a relatively good long-term uniform corrosion resistance can be achieved. In the long-term uniform corrosion test at 400°C, 10.3MPa, and 300 days, the corrosion appearance is a black and shiny oxide film, without white spots, grayish white, yellow-brown and other uneven corrosion phenomena; but it still does not achieve the best effect, and corrosion weight gain is still not the best solution.

[0025] ③ Then when Cu and Ni are added to the second-generation improved Zr-4 alloy, and the addition of Cu and Ni is reduced to (20-80) ppm, a relatively good long-term uniform corrosion resistance can be achieved. In the long-term uniform corrosion test at 400°C, 10.3MPa, and 300 days, the corrosion appearance is a black and shiny oxide film, without white spots, grayish white, yellow-brown and other uneven corrosion phenomena; but it still does not achieve the best effect, and corrosion weight gain is still not the best solution.

[0026] ④Finally, when W, Cu and Ni are added to the second-generation improved Zr-4 alloy, and the addition of W is reduced to (20-90) ppm, and the addition of Cu and Ni is reduced to (20-80) ppm, the uniform corrosion resistance of zirconium alloy can be significantly improved. In the long-term uniform corrosion test at 400℃, 10.3MPa and 300 days, the corrosion appearance is a black and bright oxide film, without white spots, grayish white, yellowish brown and other uneven corrosion phenomena. When the long-term uniform corrosion is further extended to 600 days, the corrosion appearance is still a black and bright oxide film, without white spots, grayish white, yellowish brown and other uneven corrosion phenomena; and the addition of Cu element significantly inhibits the increase in hydrogen absorption rate caused by the addition of Ni element, and its hydrogen absorption rate is not significantly improved; it exceeds the long-term uniform corrosion resistance of most third-generation zirconium alloys.

[0027] The existing technologies all use the second phase strengthening effect to improve the uniform corrosion performance of zirconium alloys, such as the Zr(Fe, Cr)2 second phase in Zr-4 alloy, the Zr(Nb, Fe)2 second phase and the (Zr, Nb)2Fe second phase in Zirlo and N36 alloys. By controlling the processing technology, these second phases are uniformly dispersed in the zirconium alloy. The "Zener effect" will cause these second phases to be pinned in large quantities at the grain boundaries of the zirconium alloy. When the α-Zr phase of the zirconium alloy with a close-packed hexagonal structure undergoes an oxidation-reduction reaction with water to generate a tetragonal zirconium oxide, the second phase at the grain boundary will produce compressive stress on the tetragonal structure. A large number of tetragonal structures are closely arranged under compressive stress, delaying the transformation of the tetragonal structure caused by long-term corrosion of zirconium water into a monoclinic structure, thereby slowing down the corrosion of the zirconium alloy. However, the amount of second phase precipitation is ultimately limited, and the strengthening effect of the second phase is ultimately limited. When the tetragonal oxide of the zirconium alloy has been corroded for a long time to two or three transition cycles, the compressive stress accumulates to the bearing limit of the tetragonal structure, causing the tetragonal structure to transform into an unstable monoclinic structure, and the effect of delaying the corrosion transition deterioration is still limited.

[0028] Therefore, when the present invention adds trace amounts of W, Cu and Ni elements to the second-generation improved Zr-4 alloy, a Zr-W-Cu-Ni substitution solid solution is formed in the zirconium alloy, and the solid solution strengthening effect stabilizes the α-Zr phase of the zirconium alloy. When the α-Zr phase of the close-packed hexagonal structure undergoes an oxidation-reduction reaction with water to generate a tetragonal zirconium oxide, the solid solution strengthening effect stabilizes the tetragonal structure of the zirconium oxide, and promotes the arrangement of the tetragonal structure to be more regular, which is more compact and more stable, and avoids the accumulation of compressive stress between the tetragonal structures under corrosion; significantly slows down the transformation of the tetragonal structure caused by long-term corrosion of zirconium water into an unstable monoclinic structure, thereby significantly slowing down the corrosion of the zirconium alloy. In addition, the Ni element can also effectively combine the hydrogen element released by the oxidation-reduction reaction of zirconium water, slow down the generation of zirconium hydride, and slow down the corrosion rate of the zirconium alloy; and the oxide structure formed by the W element, Cu element and Ni element is more stable, which can also effectively slow down the corrosion of the zirconium alloy.

[0029] 3. The third generation improved Zr-4 alloy provided by the present invention, on the basis of the second generation improved Zr-4 alloy, adds trace amounts of W element, Cu element, and Ta element to significantly improve the nodules corrosion resistance of the zirconium alloy, especially the 200h corrosion resistance. Specifically: in the second generation improved Zr-4 alloy, the addition of (20 to 200) ppm of Cu element alone has no obvious effect on improving the nodules corrosion resistance of the zirconium alloy, and there is no obvious regularity in the effect on the nodules corrosion resistance of the zirconium alloy. In the second generation improved Zr-4 alloy, the addition of (20 to 200) ppm of W element alone can improve the nodules corrosion resistance of the zirconium alloy, and the improvement effect will increase significantly with the increase of W element; however, the thermal neutron absorption cross section of the W element is very large, and excessive addition of the W element will significantly reduce the nuclear performance of the zirconium alloy; when the addition of the W element is reduced to no more than 90ppm, there is no obvious effect on the thermal neutron absorption cross section and nuclear performance of the zirconium alloy. The second generation improved Zr-4 alloy can improve the nodular corrosion resistance of zirconium alloy by adding (20-200) ppm Ta element alone. The improvement effect will increase with the increase of tantalum element, but the improvement effect is still not obvious enough. In this regard, the inventors of this application conducted the following research:

[0030] ⑤ When W element and Ta element are first added to the second-generation improved Zr-4 alloy, and the addition amount of tungsten element and tantalum element is reduced to the range of (20~90) ppm, the nodular corrosion resistance of zirconium alloy can be significantly improved; in the nodular corrosion test at 500℃, 10.3MPa, and 8h, the corrosion appearance is a black and shiny oxide film without nodular spots; further nodular corrosion to 100h, most samples still maintain the corrosion appearance of black and shiny oxide film, but a small number of nodular spots appear in very few samples.

[0031] ⑥ When Ta and Cu elements are added to the second-generation improved Zr-4 alloy together, and the Ta addition amount is reduced to the range of (20-90) ppm, and the Cu addition amount is reduced to the range of (20-80) ppm, the nodular corrosion resistance of the zirconium alloy can be significantly improved; in the nodular corrosion test at 500℃, 10.3MPa, and 8h, the corrosion appearance is a black and shiny oxide film without nodular spots; further nodular corrosion to 100h, most samples still maintain the corrosion appearance of a black and shiny oxide film, but a small number of nodular spots appear in very few samples.

[0032] ⑦ Then, when W and Cu elements are added to the second-generation improved Zr-4 alloy, and the amount of tungsten added is reduced to the range of (20-90) ppm, and the amount of Cu added is reduced to the range of (20-80) ppm, the nodular corrosion resistance of the zirconium alloy can be significantly improved; in the nodular corrosion test at 500℃, 10.3MPa, and 8h, the corrosion appearance is a black and shiny oxide film without nodular spots; further nodular corrosion to 200h, the corrosion appearance is still a black and shiny oxide film, but the nodular corrosion weight gain is still significantly higher than that of the third-generation zirconium alloy; the nodular corrosion resistance is close to the level of the third-generation zirconium alloy.

[0033] ⑧ Finally, when W, Cu and Ta are added to the second-generation improved Zr-4 alloy together, and the addition amounts of W and Ta are reduced to (20-90) ppm, and the addition amount of Cu is reduced to (20-80) ppm, the nodular corrosion resistance of the zirconium alloy can be significantly improved; in the nodular corrosion test at 500°C, 10.3MPa, and 8h, the corrosion appearance is a black and shiny oxide film without nodular spots; further nodular corrosion is carried out for 200h, and the corrosion appearance is still a black and shiny oxide film without nodular spots. The nodular corrosion weight gain is very close to that of the third-generation zirconium alloy, and the nodular corrosion resistance reaches the level of the third-generation zirconium alloy.

[0034] Therefore, when the present invention adds trace amounts of W elements, Cu elements, and Ta elements to the second-generation improved Zr-4 alloy, a Zr-W-Cu-Ta substitution solid solution is formed in the zirconium alloy, and the solid solution strengthening effect stabilizes the α-Zr phase of the zirconium alloy. When the α-Zr phase of the close-packed hexagonal structure undergoes an oxidation-reduction reaction with water to generate a tetragonal zirconium oxide, the solid solution strengthening effect stabilizes the tetragonal structure of the zirconium oxide, and promotes the arrangement of the tetragonal structure to be more regular, which is more compact and more stable, and avoids the accumulation of compressive stress between the tetragonal structures under corrosion; it significantly slows down the transformation of the tetragonal structure caused by long-term corrosion of zirconium water into an unstable monoclinic structure, thereby significantly slowing down the corrosion of the zirconium alloy. In addition, the W element, the Cu element, and the Ta element can also effectively form an electrochemical protection effect, form a potential balance, further slow down the oxidation-reduction reaction rate of the zirconium alloy and water, and effectively slow down the corrosion of the zirconium alloy. In addition, the oxide structure formed by the W element, the Cu element, and the Ta element is more stable, and can also effectively slow down the corrosion of the zirconium alloy.

[0035] 4. Improvement of comprehensive corrosion performance of Zr-4 alloy by adding W element:

[0036] The present invention uses tungsten trioxide (WO3), blue tungsten oxide (W 20 O 58 ) can significantly improve the comprehensive corrosion resistance of zirconium alloys. This is because: the melting point of W is very high, reaching 3410℃, and vacuum consumable arc melting cannot melt tungsten metal and its alloys. Therefore, W is usually not added in zirconium alloy research. However, the melting point of tungsten trioxide (WO3) is 1473℃, and the melting point of blue tungsten oxide (W 20 O 58 ) has a melting point of 1476°C, which is lower than the melting point of zirconium metal 1852°C, which can ensure that the zirconium alloy is completely melted during the vacuum consumable arc melting process, and tungsten trioxide (WO3), blue tungsten oxide (W 20 O 58 ) has an orthorhombic crystal structure above 330°C, which is similar to the crystal structure of the oxide film produced after zirconium water corrosion. It is beneficial to stabilize the oxide film produced after zirconium water corrosion and ultimately improve the corrosion resistance of zirconium alloy.

[0037] 5. Ta and W elements improve the high temperature mechanical properties of Zr-4 alloy:

[0038] The existing second-generation improved Zr-4 alloy alone adds a trace amount (20-80) ppm of W element, which can slightly improve the high-temperature mechanical properties of zirconium alloy, slightly improve the thermal creep performance and high-temperature fatigue performance, and significantly improve the high-temperature wear resistance. The existing second-generation improved Zr-4 alloy alone adds a trace amount (20-200) ppm of Ta element, which can significantly improve the high-temperature mechanical properties of zirconium alloy, especially significantly improve the thermal creep performance, including uniaxial tensile creep and pipe internal pressure creep; and significantly improve the high-temperature fatigue performance, including uniaxial tension and compression fatigue and internal pressure fatigue, and the improvement effect is quite obvious.

[0039] Through systematic research, the present invention has found that in the second-generation improved Zr-4 alloy, when the addition amount of Ta and W elements is reduced to the range of (20-90) ppm, the high-temperature mechanical properties of the zirconium alloy can be significantly improved, especially the thermal creep performance, including uniaxial tensile creep and pipe internal pressure creep; and the high-temperature fatigue performance, including uniaxial tension and compression fatigue and internal pressure fatigue; and the high-temperature wear resistance is also significantly improved; the high-temperature mechanical properties of most third-generation zirconium alloys are exceeded. This is because: when trace amounts of Ta and W are added to the second-generation improved Zr-4 alloy, a Zr-Ta-W substitutional solid solution is formed in the zirconium alloy, and the solid solution strengthening effect stabilizes the α-Zr phase of the zirconium alloy, causing the lattice distortion energy to increase significantly, and the dislocation density of the crystal and the grain boundary is further increased, thereby effectively improving the thermal creep performance, high-temperature fatigue performance and other high-temperature mechanical properties of the zirconium alloy.

[0040] Among them, the Ta element can be added in the form of tantalum intermediate alloys such as aluminum-tantalum alloy, copper-tantalum alloy, nickel-tantalum alloy, niobium-tantalum alloy, etc.; when the Ta element is added in the form of tantalum intermediate alloy, if the Al element and Nb element are inevitably introduced, their contents should be controlled within the following ranges: Al≤0.01%, Nb≤0.015%.

[0041] In a third aspect, the present invention provides a method for preparing a third-generation improved Zr-4 alloy material. The third-generation improved Zr-4 alloy ingot prepared by the preparation method as described above can be processed into zirconium alloy materials such as pipes, bars, plates, wires or foil strips through forging, quenching, hot working, cold working and heat treatment.

[0042] In addition, the present invention also provides an application of the third-generation improved Zr-4 alloy as described above in fuel cladding materials and structural materials for long-life nuclear reactors.

[0043] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0044] The present invention is based on the second-generation improved Zr-4 alloy, and slightly reduces the tin content to improve the nodular corrosion resistance of the Zr-4 alloy; and through the improvement of the addition amount and / or addition method of multiple trace elements such as "the addition method and amount of O element, the addition amount of W element, Cu element, Ni element, Ta element, the addition method of W element, the addition method of Ta element", the various properties of the finally formed third-generation improved Zr-4 alloy far exceed the level of the second-generation improved Zr-4 alloy, and fully reach the level of the third-generation zirconium alloy. In particular, the key technical difficulty of Zr-4 alloy's inability to resist nodular corrosion has been overcome, and the level of the third-generation zirconium alloy has been reached: its uniform corrosion performance significantly exceeds the third-generation zirconium alloy; its high-temperature resistant mechanical properties exceed the third-generation zirconium alloys such as M5 and Zirlo, and reach the level of the third-generation zirconium alloys such as N36 and N18. Therefore, the comprehensive performance of the third-generation improved Zr-4 alloy provided by the present invention has reached the standard of the third-generation zirconium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] The accompanying drawings are incorporated in and constitute a part of this specification and, together with the description, serve to explain the principles of the present invention.

[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0047] Figure 1 A flow chart of a method for preparing a third-generation improved Zr-4 alloy provided by the present invention;

[0048] Figure 2 Corrosion weight gain curves of the pipes prepared in Examples 1 to 3 and the plates prepared in Examples 4 to 6 under long-term uniform corrosion performance test conditions (400°C / 10.3MPa);

[0049] Figure 3 The corrosion weight gain curves of the pipes prepared in Examples 1 to 3 and the plates prepared in Examples 4 to 6 under the nodular corrosion performance test conditions (500°C / 10.3MPa). DETAILED DESCRIPTION

[0050] Here, exemplary embodiments will be described in detail, and the embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are only examples consistent with some aspects of the present invention described in detail in the appended claims.

[0051] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0052] Example 1

[0053] The present embodiment provides a third generation improved Zr-4 alloy (I), which is composed of the following components in mass percentage: Sn 1.1%, Fe 0.23%, Cr 0.10%, O 0.14%, W 0.005%, Cu 0.005%, Ni 0.005%, Ta0.005%, and the balance is Zr and unavoidable impurities.

[0054] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (I), which specifically includes the following steps:

[0055] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with zirconium foil, and cold pressing to prepare electrode blocks;

[0056] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0057] Step 3: performing vacuum consumable arc melting three times on the zirconium alloy consumable electrode to obtain a third-generation improved Zr-4 alloy ingot (I).

[0058] Wherein, in step 1, the weight of the raw materials required for each additional element (the weight of the raw materials required for the additional element = the total weight × the weight percentage of the additional element) and the weight of the nuclear grade zirconium sponge (the weight of the nuclear grade zirconium sponge = the total weight - the weight of all added elements) are calculated according to the total weight of the third-generation improved Zr-4 alloy (I) to be prepared.

[0059] Specifically, the O element is added by tin dioxide (SnO2); when the Ta element is added by aluminum-tantalum alloy, the Al element is inevitably introduced, and the mass percentage of the Al element should be ≤0.01%; the W element is added by tungsten trioxide (WO3).

[0060] In addition, the third generation improved Zr-4 alloy ingot (I) is processed into a pipe (I) by forging, quenching, hot working, cold working and heat treatment.

[0061] Example 2

[0062] The present embodiment provides a third generation improved Zr-4 alloy (II), which is composed of the following components in mass percentage: Sn 1.0%, Fe 0.22%, Cr 0.11%, O 0.15%, W 0.006%, Cu 0.004%, Ni 0.004%, Ta0.006%, and the balance is Zr and unavoidable impurities.

[0063] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (II), which specifically includes the following steps:

[0064] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with zirconium foil, and cold pressing to prepare electrode blocks;

[0065] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0066] Step 3: performing vacuum consumable arc melting three times on the zirconium alloy consumable electrode to obtain a third-generation improved Zr-4 alloy ingot (II).

[0067] In step 1, SnO is used to add O element; Cu-Tantalum alloy is used to add Ta element; and blue tungsten oxide (W 20 O 58 )Add the W element.

[0068] In addition, the third generation improved Zr-4 alloy ingot (II) is processed into a pipe (II) by forging, quenching, hot working, cold working and heat treatment.

[0069] Example 3

[0070] This embodiment provides a third-generation improved Zr-4 alloy (III), which is composed of the following components in mass percentage: Sn 1.3%, Fe 0.20%, Cr 0.12%, O 0.13%, W 0.007%, Cu 0.003%, Ni 0.006%, Ta0.004%, and the balance is Zr and unavoidable impurities.

[0071] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (III), which specifically includes the following steps:

[0072] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with zirconium foil, and cold pressing to prepare electrode blocks;

[0073] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0074] Step 3: performing vacuum consumable arc melting three times on the zirconium alloy consumable electrode to obtain a third-generation improved Zr-4 alloy ingot (III).

[0075] In step 1, Sn3O4 is used to add O element; Ni-Tantalum alloy is used to add Ta element; and blue tungsten oxide (W 20 O 58 )Add the W element.

[0076] In addition, the third generation improved Zr-4 alloy ingot (III) is processed into a pipe (III) by forging, quenching, hot working, cold working and heat treatment.

[0077] Example 4

[0078] The present embodiment provides a third generation improved Zr-4 alloy (four), which is composed of the following components in mass percentage: Sn 1.2%, Fe 0.22%, Cr 0.10%, O 0.13%, W 0.004%, Cu 0.006%, Ni 0.003%, Ta0.007%, and the balance is Zr and unavoidable impurities.

[0079] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (IV), which specifically includes the following steps:

[0080] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with tin foil, and cold pressing to prepare electrode blocks;

[0081] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0082] Step 3: performing vacuum consumable arc melting on the zirconium alloy consumable electrode four times to obtain a third-generation improved Zr-4 alloy ingot (four).

[0083] In step 1, O element is added by tin dioxide (SnO2); when Ta element is added by niobium-tantalum alloy, Nb element will inevitably be introduced, and the mass percentage of Nb element should be ≤0.015%; W element is added by tungsten trioxide (WO3).

[0084] In addition, the third generation improved Zr-4 alloy ingot (IV) is processed into a plate (IV) by forging, quenching, hot working, cold working and heat treatment.

[0085] Example 5

[0086] The present embodiment provides a third generation improved Zr-4 alloy (V), which is composed of the following components in mass percentage: Sn 1.1%, Fe 0.23%, Cr 0.09%, O 0.14%, W 0.006%, Cu 0.004%, Ni 0.005%, Ta0.005%, and the balance is Zr and unavoidable impurities.

[0087] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (V), which specifically includes the following steps:

[0088] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with tin foil, and cold pressing to prepare electrode blocks;

[0089] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0090] Step 3: performing vacuum consumable arc melting on the zirconium alloy consumable electrode four times to obtain a third-generation improved Zr-4 alloy ingot (V).

[0091] In step 1, the O element is added by tin monoxide (SnO); the Ta element is added by copper-tantalum alloy; and the W element is added by tungsten trioxide (WO3).

[0092] In addition, the third generation improved Zr-4 alloy ingot (V) is processed into a plate (V) by forging, quenching, hot working, cold working and heat treatment.

[0093] Example 6

[0094] The present embodiment provides a third generation improved Zr-4 alloy (six), which is composed of the following components in mass percentage: Sn 0.9%, Fe 0.21%, Cr 0.11%, O 0.14%, W 0.005%, Cu 0.005%, Ni 0.004%, Ta 0.006%, and the balance is Zr and unavoidable impurities.

[0095] In addition, this embodiment provides a method for preparing a third-generation improved Zr-4 alloy (VI), which specifically includes the following steps:

[0096] Step 1, weighing and mixing the raw materials according to the required mass percentage, wrapping the raw materials with tin foil, and cold pressing to prepare electrode blocks;

[0097] Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere;

[0098] Step 3: performing vacuum consumable arc melting on the zirconium alloy consumable electrode four times to obtain a third-generation improved Zr-4 alloy ingot (six).

[0099] In step 1, SnO2 is used to add O element; Ni-Tantalum alloy is used to add Ta element; and blue tungsten oxide (W 20 O 58 )Add the W element.

[0100] In addition, the third generation improved Zr-4 alloy ingot (six) is processed into a plate (six) by forging, quenching, hot working, cold working and heat treatment.

[0101] It should be noted that the third-generation improved Zr-4 alloy ingots obtained in the above-mentioned embodiments 1 to 6 are first forged at 800°C to 1100°C, then quenched at 1000°C to 1200°C, and then hot-worked at 600°C to 700°C (wherein the pipe is hot extruded and the plate is hot rolled), and then subjected to multiple cold rolling and corresponding annealing at a temperature of 500°C to 650°C, and surface treatment and other processes to prepare the corresponding third-generation improved Zr-4 alloy pipes or plates.

[0102] In order to verify the effectiveness of the technical solution provided by the present invention, the pipes prepared in the above-mentioned embodiments 1 to 3 and the plates prepared in embodiments 4 to 6 were respectively subjected to long-term uniform corrosion performance test, nodular corrosion performance test, and thermal creep performance test. The specific test methods are as follows:

[0103] ① Long-term uniform corrosion performance test: The pipes in Examples 1 to 3, the plates in Examples 4 to 6, N36 alloy pipes, Zirlo alloy pipes, M5 alloy pipes, N18 alloy plates, and second-generation improved Zr-4 alloy plates were subjected to long-term uniform corrosion tests at 400°C, 10.3 MPa, for 300 days and 600 days. The test results are shown in Table 1.

[0104] Table 1 Long-term uniform corrosion performance test results

[0105]

[0106]

[0107] It can be seen from Table 1 that, compared with N36 alloy pipe, Zirlo alloy pipe, M5 alloy pipe, N18 alloy plate, and second-generation improved Zr-4 alloy plate, the third-generation improved Zr-4 alloy pipe prepared in Examples 1 to 3 of the present invention and the third-generation improved Zr-4 alloy plate prepared in Examples 4 to 6 have excellent long-term uniform corrosion resistance. After a long-term uniform corrosion test at 400°C, 10.3MPa, and 300 days, the corrosion weight gain is only 88mg / dm 2 ~97 mg / dm 2 (See Figure 2 ), the corrosion appearance is black and shiny; and in the long-term uniform corrosion test for 600 days, the corrosion weight gain is still maintained at 146mg / dm 2 ~160 mg / dm 2 The corrosion appearance is black and shiny, and the long-term uniform corrosion performance is significantly better than that of the second-generation Zr-4 alloy and the third-generation zirconium alloy; and there is no uneven corrosion phenomenon such as white corrosion spots and brown corrosion spots that appear in the second-generation improved Zr-4 and the third-generation M5 alloy.

[0108] ② Nodular corrosion performance test: The pipes in Examples 1 to 3, the plates in Examples 4 to 6, N36 alloy pipes, Zirlo alloy pipes, M5 alloy pipes, N18 alloy plates, and second-generation improved Zr-4 alloy plates were all subjected to nodular corrosion tests at 500°C, 10.3MPa, for 8h, 32h, and 200h. The test results are shown in Table 2.

[0109] Table 2 Nodular corrosion performance test results

[0110]

[0111]

[0112] It can be seen from Table 2 that, compared with N36 alloy pipe, Zirlo alloy pipe, M5 alloy pipe, N18 alloy plate, and second-generation improved Zr-4 alloy plate, the third-generation improved Zr-4 alloy pipe prepared in Examples 1 to 3 of the present invention and the third-generation improved Zr-4 alloy plate prepared in Examples 4 to 6 have excellent nodular corrosion resistance: nodular corrosion resistance at 500°C, 10.3MPa, 8h, and the corrosion weight gain is only 32mg / dm 2 ~36 mg / dm 2 (See Figure 3 ), the appearance of the nodular corrosion is black and shiny, without nodular spots; and when the nodular corrosion test is carried out for 200h, the corrosion weight gain is still maintained at 145mg / dm 2 ~153 mg / dm 2 The nodular corrosion performance of the alloy has reached the level of the third-generation zirconium alloy.

[0113] ③ Thermal creep performance test: The pipes in Examples 1 to 3, the plates in Examples 4 to 6, and the N36 alloy pipes, Zirlo alloy pipes, M5 alloy pipes, N18 alloy pipes, and the second-generation improved Zr-4 alloy pipes were subjected to 400°C, 157MPa, 200h uniaxial tensile creep tests, and 400°C, 130MPa, 240h pipe internal pressure creep tests. The test results are shown in Table 3.

[0114] Table 3 Thermal creep performance test results

[0115]

[0116] It can be seen from Table 3 that, compared with N36 alloy pipe, Zirlo alloy pipe, M5 alloy pipe, N18 alloy pipe and second-generation improved Zr-4 alloy pipe, the third-generation improved Zr-4 alloy pipe prepared in Examples 1 to 3 of the present invention and the third-generation improved Zr-4 alloy sheet prepared in Examples 4 to 6 have excellent heat-resistant creep performance: after completing the uniaxial tensile creep test at 400°C, 157MPa and 200h, the steady-state creep rate is only 0.0383×10 -3 / h~0.0538×10 -3 / h, and can creep for up to 200h; after completing the internal pressure creep test of the pipe at 400℃, 130MPa, and 240h, the creep elongation is only 0.43% to 0.48%, and can creep for up to 240h.

[0117] In summary, the third-generation improved Zr-4 alloy provided by the present invention has excellent resistance to uniform corrosion and nodular corrosion, as well as resistance to high-temperature fatigue, creep, wear and the like; its long-term uniform corrosion resistance and comprehensive high-temperature mechanical properties are better than those of third-generation zirconium alloys such as M5, Zirlo, and N36, and its 200h nodular corrosion performance reaches the level of third-generation zirconium alloys, and its comprehensive performance reaches the level of third-generation zirconium alloys such as M5, Zirlo, and N36; its processing performance is equivalent to that of M5, and is better than that of third-generation zirconium alloys such as Zirlo and N36; it is suitable for use as a fuel cladding material and structural material for long-life nuclear reactors.

[0118] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention.

[0119] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.

Claims

1. A third generation improved Zr-4 alloy, characterized in that: It is composed of the following components in mass percentage: Sn 0.85%-1.50%, Fe 0.18%-0.24%, Cr 0.07%-0.13%, O 0.09%-0.16%, W 0.002%-0.009%, Cu 0.002%-0.008%, Ni 0.002%-0.008%, Ta 0.002%-0.009%, and the balance is Zr and unavoidable impurities.

2. The third generation improved Zr-4 alloy according to claim 1, characterized in that: It is composed of the following components in mass percentage: Sn 1.0%-1.2%, Fe 0.21%-0.24%, Cr0.08%-0.11%, O 0.13%-0.15%, W0.004%-0.007%, Cu 0.003%-0.005%, Ni 0.004%-0.006%, Ta 0.005%-0.008%, and the balance is Zr and unavoidable impurities.

3. The third generation improved Zr-4 alloy according to claim 1, characterized in that: The following components are present in percentage by weight Composition: Sn 1.1%~1.3%, Fe 0.20%~0.23%, Cr0.09%~0.12%, O 0.14%~0.16%, W0.003%~0.006%, Cu 0.004%~0.006%, Ni 0.003%~0.005%, Ta 0.004%~0.007%, the balance is Zr and unavoidable impurities.

4. The third generation improved Zr-4 alloy according to claim 1, characterized in that: The following components are present in percentage by weight Composition: Sn 1.2%~1.4%, Fe 0.19%~0.22%, Cr0.11%~0.13%, O 0.12%~0.14%, W0.005%~0.008%, Cu 0.003%~0.005%, Ni 0.005%~0.007%, Ta 0.003%~0.006%, the balance is Zr and unavoidable impurities.

5. The third generation improved Zr-4 alloy according to claim 1, characterized in that: It is composed of the following components in mass percentage: Sn 1.3%~1.5%, Fe 0.21%~0.24%, Cr0.09%~0.12%, O 0.12%~0.14%, W0.004%~0.007%, Cu 0.004%~0.006%, Ni 0.004%~0.006%, Ta 0.004%~0.007%, and the balance is Zr and unavoidable impurities.

6. The third generation improved Zr-4 alloy according to claim 1, characterized in that: It is composed of the following components in mass percentage: Sn 0.9%-1.1%, Fe 0.20%-0.23%, Cr0.08%-0.11%, O 0.13%-0.15%, W0.003%-0.006%, Cu 0.005%-0.007%, Ni 0.003%-0.005%, Ta 0.005%-0.008%, and the balance is Zr and unavoidable impurities.

7. A method for preparing a third generation improved Zr-4 alloy, characterized in that: The specific steps include: Step 1, compounding and mixing the elements in the third generation improved Zr-4 alloy according to the mass percentage of each element in any one of claims 1 to 6, and pressing them into electrode blocks; Step 2, welding a plurality of electrode blocks into a zirconium alloy consumable electrode under the protection of an inert atmosphere; Step 3: performing vacuum consumable arc melting on the zirconium alloy consumable electrode for 2 to 4 times to obtain a third-generation improved Zr-4 alloy ingot.

8. The method for preparing the third generation improved Zr-4 alloy according to claim 7, characterized in that: In step 1, the O element is added in the form of tin metal oxide; the Ta element is added in the form of tantalum master alloy; and the W element is added in the form of tungsten metal oxide.

9. A method for preparing a third generation improved Zr-4 alloy material, characterized in that: The third generation improved Zr-4 alloy ingot prepared by the preparation method as described in claim 7 or 8 is processed into pipes, bars, plates, wires or foil strips by forging, quenching, hot working, cold working and heat treatment.

10. Use of the third generation improved Zr-4 alloy as claimed in any one of claims 1 to 6 in fuel cladding materials and structural materials for long-life nuclear reactors.

Citation Information

Patent Citations

  • Corrosion-resistant nuclear zirconium alloy material and preparation method thereof

    CN113355561A

  • Zirconium alloy with tungsten and nickel

    CN1157640A